Treatment of Frequent or Chronic Primary Headaches in Children and Adolescents: Focus on Acupuncture - Ilaria Bonemazzi; Magherita Nosadini; Maria Federica Pelizza; Chiara Paolin; Elena Cavaliere; Stefano Sartori; Irene Toldo (MDPI AG, 2023)
Background: Acupuncture is a spreading and promising intervention, which has proven to be very useful in the treatment and prevention of chronic pain, in particular chronic headaches, in adults; the literature about the treatment of pediatric chronic headaches is scarce. In addition, few guidelines advise its use in children. The aim of this review is to collect all relevant studies with available data about the use, effect, and tolerability of acupuncture as a treatment for pediatric primary headaches. Methods: This is a narrative review based on eight studies selected from 135 papers including pediatric cases treated with acupuncture for headache. Results: Despite the differences in tools, procedures, and application sites, acupuncture demonstrated a positive effect on both the frequency and intensity of headaches and was well tolerated. There are no studies considering the long-term efficacy of acupuncture. Conclusion: Further additional studies are needed on acupuncture in children and adolescents, with larger series and standardized procedures, in order to better assess efficacy, tolerability, and long-term prognosis and to define guidelines for the use of this promising and safe treatment. It is particularly relevant to identify safe and well-tolerated treatment options in pediatric patients affected by recurrent and debilitating headaches.